IMPORTÂNCIA DA SEGURANÇA CIBERNÉTICA NA ESTRUTURAÇÃO DE DE DEFESAS ONLINES NO ÂMBITO MILITAR NACIONAL E INTERNACIONAL - de Camargo Fantin, Vinicius; Surdi, João Victor; Oliveira, Gabriel de; Borga, Rafael Simon; Wonzoski, Fabiano Oliveira (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2025)
The rapid advancement of information and communication technologies has reshaped the dynamics of modern conflicts, with cyberspace emerging as a crucial battlefield alongside land, sea, air, and space. This paper examines the strategic role of cybersecurity in national and international defense, analyzing how digital attacks and cyber strategies influence the balance of power and redefine sovereignty in contemporary hybrid conflicts. The Russia–Ukraine war is presented as a key example, illustrating how cyber operations such as espionage, disinformation, sabotage, and persistent threats can shape outcomes even before physical clashes occur. The objective is to analyze how reliance on digital infrastructures creates both opportunities and vulnerabilities, making cybersecurity a central element of military strategy and geopolitical stability. Methodologically, the study is based on literature review and data analysis on cyber militarism, invasion techniques, protection mechanisms, and data breaches. These factors demonstrate that nations with stronger digital resilience are better positioned to withstand external threats and protect sovereignty. Results highlight the escalation of cyber incidents during the Russia–Ukraine conflict. According to the 2023 report Cyber Dimensions of the Armed Conflict in Ukraine, Ukraine faced 97 cyberattacks, Russia 13, and other countries 472. About 89% were distributed denial-of-service (DDoS) attacks, targeting mainly public administration, media, information technology, financial, and trade sectors. Russian-sponsored groups such as Fancy Bear, Sandworm, and CyberBerkut, with support from agencies like the FSB and GRU, carried out coordinated cyber operations preceding military invasions. Tools such as BlackEnergy, X-Agent, and KillDisk enabled espionage, sabotage, and data destruction, while phishing and spear-phishing revealed the importance of social engineering in cyber warfare. Findings show that cybersecurity has evolved from a technical safeguard into a strategic asset vital for defense and international security. The analysis demonstrates that digital supremacy can be as decisive as conventional military force, shaping both conflicts and geopolitical balance. Cybersecurity must therefore be recognized as a central dimension of sovereignty in the twenty-first century. The study concludes by recommending future research on international cooperation mechanisms in cyber defense and the legal and ethical challenges of cyber warfare under international law. Understanding these dynamics is essential for creating effective policies to counter increasingly sophisticated and persistent cyber threats in global security.